2004
DOI: 10.1002/em.10205
|View full text |Cite
|
Sign up to set email alerts
|

Urinary mutagenesis and fried red meat intake: Influence of cooking temperature, phenotype, and genotype of metabolizing enzymes in a controlled feeding study

Abstract: Meat cooked at high temperatures contains potential carcinogenic compounds, such as heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs). Samples from a 2-week controlled feeding study were used to examine the relationship between the intake of mutagenicity from meat fried at different temperatures and the levels of mutagenicity subsequently detected in urine, as well as the influence of the genotype of drug metabolizing enzymes on urinary mutagenicity. Sixty subjects consumed ground beef pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…11 The genotype/phenotype association for the three most common polymorphisms of the UGT1A1 gene demonstrates that these genetic factors modulate the formation of this biomarker, N-OH-PhIP-N 2 G. Therefore, the UGT1A1 status is most likely to influence the level of exposure to N-OH-PhIP and potentially the risk of cancer through dietary exposure to HCAs. Consistent with this hypothesis, Peters and coworkers 50 recently showed in a controlled feeding study, that the UGT1A1*28 allele modifies the effect of intake of meat cooked at high temperature, generating HCAs, on urinary mutagenicity (a biological measurement of exposure). Given the strong biological plausibility for the role of UGT1A1 in the etiology of cancer, epidemiologic studies in populationbased samples with detailed exposure assessment are needed to fully explore this hypothesis and have recently been initiated.…”
Section: Discussionmentioning
confidence: 75%
“…11 The genotype/phenotype association for the three most common polymorphisms of the UGT1A1 gene demonstrates that these genetic factors modulate the formation of this biomarker, N-OH-PhIP-N 2 G. Therefore, the UGT1A1 status is most likely to influence the level of exposure to N-OH-PhIP and potentially the risk of cancer through dietary exposure to HCAs. Consistent with this hypothesis, Peters and coworkers 50 recently showed in a controlled feeding study, that the UGT1A1*28 allele modifies the effect of intake of meat cooked at high temperature, generating HCAs, on urinary mutagenicity (a biological measurement of exposure). Given the strong biological plausibility for the role of UGT1A1 in the etiology of cancer, epidemiologic studies in populationbased samples with detailed exposure assessment are needed to fully explore this hypothesis and have recently been initiated.…”
Section: Discussionmentioning
confidence: 75%
“…SNPs in transcription factor binding sites may affect the binding of transcription factors, lead to differences in gene expression and phenotypes, and therefore affect response and susceptibility to environmentally induced disease (2)(3)(4)(5)(6)(7)(8)30,31). Computational methods for predicting the effects of genetic variation are increasingly important because of the rapidly growing catalog of SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples include a SNP that causes human α-thalassemias by creating a new binding site for erythroid transcription factor GATA-1 in the upstream of α-globin gene (2) and a SNP (-43C->T) in the proximal Sp1 site of the human low density lipoprotein receptor promoter results in heterozygous familial hypercholesterolemia (3). The UGT1A1 gene has a TATA box polymorphism that reduces expression of UGT1A1, leading to Gilbert's syndrome (a common form of hyperbilirubinemia) (4,5), and has also been associated with higher levels of mutagens in the urine (6). The steroid metabolism gene CYP17 has a GC box polymorphism in its proximal promoter that has been associated with higher levels of circulating estradiol (7) and with differences in bone mineral density (8).…”
Section: Introductionmentioning
confidence: 99%
“…Innocenti et al reported that, compared to *1/*1 and *1/*28 individuals, *28/*28 individuals had a higher prevalence of grade 4 neutropenia and a higher area under the curve (AUC) for the irinotecan metabolite SN-38 that requires glucuronidation in order to be cleared effectively [61]. Peters et al showed that, with exposure to well-cooked red meat (a source of mutagenic compounds) in a controlled feeding study, individuals with the *1/*28 and *28/ *28 genotypes had a higher urinary mutagenicity index than did individuals with the *1/*1 genotypes [62]. The authors suggested that greater amounts of the mutagens were being excreted in the freeform, rather than being glucuronidated and deactivated.…”
Section: Udp-glucuronosyltransferasesmentioning
confidence: 99%